514 Audit to Assess Negative Appendicectomy Rate (NAR) in Adult Patients in The Leicester Royal Infirmary (LRI). (4th May 2021) - Baguley, M; Palser, T
Abstract: Aim: Determine the NAR rate in Leicester Royal Infirmary (LRI) and compare to the national average (20%) Additional objectives: False-positive rate for USS and CT in assessing potential appendicitis Assess in what percentage of USS the appendix is visualised Method: This was a retrospective audit which considered all patients admitted over a three-month period to the LRI with suspected appendicitis. Data was collected on patients proceeding to surgery, and then whether their histology was pathological. Results: 318 patients were included, of which 80 proceeded to surgery. Objective 1 - NAR of 5% (4/80) Secondary objective 1 USS False-positive rate 5.4% (2/37) CT False-positive rate 2.3% (1/43) Secondary objective 2 - Appendix visualised in 29.3% (48/164) of Ultrasounds Conclusions: This audit has demonstrated that both USS and CT have a very low false-positive rate in assessment of appendicitis; however, USS visualises the appendix in less than 30% of cases. I believe the pathway should be altered to remove USS scanning for obese patients where the appendix is difficult to visualise; or in older patients, where there is less concern in using the CT modality.